Distribution of Liquid Flow Rates in the Process of Bubbling with Gas Through Gas-Permeable Inserts; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Gizatulin R. A. Rinat Akramovich; Valuev D. V. Denis Viktorovich; Dariev R. S.; Trifonov V. A. Vladimir Aleksandrovich; Borovikov I. F. (2016, 2016)
Title screen